1990
DOI: 10.1111/j.1365-2214.1990.tb00670.x
|View full text |Cite
|
Sign up to set email alerts
|

From the other side: parents’views of their early contacts with health professionals

Abstract: The parents of 84 school-age children with cerebral palsy were interviewed about their early experiences of dealing with health professionals. Seventy per cent of families expressed dissatisfaction with some aspects of their contact with the health services during the initial period of diagnosis and referral. Lack of explanation, either about the child's condition or the reasons for follow-up, was the commonest complaint (58%), followed by having their worries dismissed by doctors and the need to make repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…Although other researchers have discussed dissatisfaction (Larsen et al, 1979;McKay & Hensey, 1990;McNaughton, 1994;Weller, 1991;Williams, 1994;Zapka et al, 1995), studies have not explicitly examined the elements of service delivery that underlie the states of dissatisfaction versus satisfaction. It generally is assumed that the elements that lead to dissatisfaction are the opposite of those that lead to satisfaction.…”
Section: Elements Of Satisfaction Versus Dissatisfactionmentioning
confidence: 96%
See 3 more Smart Citations
“…Although other researchers have discussed dissatisfaction (Larsen et al, 1979;McKay & Hensey, 1990;McNaughton, 1994;Weller, 1991;Williams, 1994;Zapka et al, 1995), studies have not explicitly examined the elements of service delivery that underlie the states of dissatisfaction versus satisfaction. It generally is assumed that the elements that lead to dissatisfaction are the opposite of those that lead to satisfaction.…”
Section: Elements Of Satisfaction Versus Dissatisfactionmentioning
confidence: 96%
“…A review of the health care literature (encompassing the literature on adult and pediatric medical care and rehabilitation) revealed 21 articles providing information about the elements underlying satisfaction (Baker, 1990;Ben-Sira, 1976;Cook et al, 1986;DiMatteo & Hays, 1980;Donabedian, 1988;Doyle & Ware, 1977;Dutton et al, 1985;Forbes & Brown, 1995;Hall & Dornan, 1988;Knafl, Breitmayer, Gallo, & Zoeller, 1992;Krahn et al, 1990;Larsen et al, 1979;Mahoney, O'Sullivan, & Dennebaum, 1990;McCusker, 1984;McKay & Hensey, 1990;Murphy, Lee, Turbiville, Turnbull, & Summers, 1991;Simonian, Tarnowski, Park, & Bekeny, 1993;Ware & Snyder, 1975;Weller, 1991;Zyzanski et al, 1974). These articles mostly deal with adult patients' satisfaction with medical care, although some deal specifically with parents of children with special needs or children receiving medical care (e.g., S. Knafl et al, 1992;Mahoney et al, 1990;Murphy et al, 1991).…”
Section: Coding Schemementioning
confidence: 98%
See 2 more Smart Citations
“…Studies investigating parents' views of professional services in the early years include those by McKay and Hensey (1990), Sloper and Turner (1992), Wishart et al (1993), Haylock et al (1993) and Pimm (1996). They revealed that parents were generally dissatisfied with fragmented services and were given insufficient support and often contradictory advice.…”
Section: Parents and Professionalsmentioning
confidence: 97%